Examination of the dynamic covalent chemistry of (2 + 3)-imine cages - Schick, Tobias; Rominger, Frank; Mastalerz, Michael (The journal of organic chemistry, 2020)
The synthesis of shape-persistent organic cage compounds by the formation of imine bonds opens the possibility to realize cages of different sizes, geometries, topologies, and functions. It is generally assumed that the imine bond is rather chemically labile allowing a self-correction mechanism until thermodynamic equilibrium is reached, which is often the case if a cage is formed. However, there are some contradictory experimental data to this assumption. To get a deeper insight into the imine bond dynamics of covalent organic cages, we studied the formation and exchange of both dialdehydes and triamines of two different (2 + 3) imine cages with the aid of a deuterated dialdehyde molecular building block.